SDG16 peace and justice : challenges, actions and the way forward - Radović, Vesela (Concise guides to the United Nations Sustainable Development Goals., 2019)
SDG16 recognises the need to respond to challenges to build a peaceful and just world. In the context of a transforming global community that is increasingly faced with conflict, the threat of terrorism and political instability, this goal has become more important than ever.Peace and justice are recognized as important drivers in creating a sustainable society by bridging the Global North/South divide, the gap between rich and poor, the gap between developed and developing countries, and erasing the increased possibility of isolating marginalized groups such as migrants, woman, and disabled people. This book details how interested parties can, must and are getting ahead of the curve to promote peace, provide access to justice and build accountable institutions for all. It envisions a hopeful future in which the impacts of SDG16 are likely to be far more positive and transformational, and visible much more quickly, than we might have imagined.